ANALISIS PENGETAHUAN MANAJEMEN KEUANGAN DAN MOTIVASI TERHADAP WIRAUSAHA ANGGOTA KARANG TARUNA LINGKUNGAN GODONG KELURAHAN TAMBUSAI TENGAH - Wahyudi Wahyudi; Heffi Christya Rahayu; Ratna Dewi (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the influence of financial management knowledge and motivation on entrepreneurship among members of the Karang Taruna (Youth Organization) in the Godong Neighborhood, Tambusai Tengah Village. Entrepreneurship is an important factor in increasing economic independence and community welfare, especially among young people. This study used a quantitative approach with a survey method, where all members of the Karang Taruna were selected as respondents through a saturated sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability and supported by observation, interviews, and documentation. Data analysis techniques included classical assumption tests, multiple linear regression analysis, partial tests, simultaneous tests, and coefficients of determination using the SPSS program. The results showed that partially financial management knowledge did not have a significant effect on entrepreneurship, while motivation had a positive and significant effect on entrepreneurship. Simultaneously, financial management knowledge and motivation had a significant effect on entrepreneurship among members of the Karang Taruna in the Godong Neighborhood, Tambusai Tengah Village. The findings of this study are expected to be used as considerations in increasing youth entrepreneurship activities by strengthening motivation and improving understanding of financial management.